The Inhibitive Effect of Some Glycine Derivatives Towards the Corrosion of Aluminium in Hydrochloric Acid Solution - Al-Neami, K.Kh.; Fouda, A.S. (Asian Journal of Chemistry, 2010)
Polarization and thermometric methods have been used to study the inhibition of aluminium corrosion in HCl solution, by some glycine derivatives. The inhibition efficiencies obtained from the two methods are in good agreement and are dependent upon the concentration of the inhibitor, its molecular size and its chemical composition. The results of polarization method indicate that the compounds act as mixed inhibitors. The inhibitors appear to function through general adsorption following the Langmuir adsorption isotherm. The change in the free energy for adsorption of inhibitors has been calculated and discussed.